SALES AND DISTRIBUTION ANALYSIS, CASE STUDY IN PT. XYZ - Michael
The purpose of this thesis is to help solve one of the current existing issues of PT. Berkat Popok Bahagia which is SKUs being out of stock. It turns out that there are several reasons for this. The first reason is the amount of the stock of each SKU in the system differs from the amount of stock in the warehouse. The second reason is the demand from the distributors is not in sync with the sales and operational planning team, making it when the distributors order products (SKU) from the factory, the product is not available because it might not be in the production process. The third reason is the forecasting method that is currently being used is less suitable. These issues have to be studied and analyzed because it can become a threat to the company in the long run. The objectives of the research are to analyze and assess the current situation related to sales distribution of the company, figure out the root cause that affect the current operation of sales distribution, and to propose solutions for the company followed by the implementation plan of the solution that the company choose. The methods that are used for this thesis starts from finding the negative cumulative difference to determine which distributors are underperforming, pareto analysis to determine who the key customers are in each segment and how big their contribution are, voting method which involves the company’s stakeholders to determine the best solution that have been proposed, and comparing the forecasting accuracy of each forecasting method in the top 2 SKUs of baby care category from simple moving average method , simple exponential smoothing method and exponential smoothing with trend method. The results of the forecasting accuracy is based on the MAPE value in which lower value indicates better method. The forecasting accuracy measurement result when comparing the 3 methods between the 2 SKUs are respectively 24.3% and 20.24% for simple moving average, 20.28% and 16.19% for simple exponential smoothing and 18.07% and 15.65% for exponential smoothing with trend. The results indicate that exponential smoothing with trend provides the best performance among the three which therefore author recommend this method compared to the current simple moving average method